Membangun Digital Marketing dalam Optimalisasi Penjualan di UMKM Salad Buah dan Es Teler Widhii - Subrata, Jaka; Asmarany, Syakina Auliya; Maharani, Pratiwi Widiar (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Micro, small, and medium enterprises (UMKM) are an important sector in the Indonesian economy, but many still face obstacles in marketing their products digitally. UMKM salad buah dan es teler widhii are one of the business actors that have the potential for superior products but have not optimally utilized digital technology to increase sales. The main problems faced by UMKM salad buah dan es teler widhii are the lack of understanding in digital marketing, the absence of a website as a promotional media, not having a NIB, and not having a halal certificate. This community service activity aims to build an effective digital marketing strategy to optimize product sales in UMKM salad buah dan es teler widhii. The activities carried out include providing an understanding of digital marketing, creating a website as a promotional media for digital platforms. Creating a NIB as an official identity shows that salad buah dan es teler widhii business has been legally registered and recognized by the government, and creating a halal certificate, official evidence stating that the products sold have met halal standards in accordance with Islamic law. The results of this community service activity show an increase in the digital skills of business actors, the formation of a website that has an impact on increasing the number of consumers, and a sense of trust from consumers and potential consumers in the UMKM salad buah dan es teler widhii because of the NIB and halal certificates that prove that the UMKM has been legally registered and recognized by the government for its halalness. This community service activity has a positive impact on building UMKM to compete in the digital era and open up wider market opportunities